Law on Vietnamese Nationality - The National Assembly (2008)
Vietnamese nationality reflects the cohesive relationship betwee n individuals and the State of the Socialist Republic of Vietnam, giving rise to rights and obligations of Vietnamese citizens toward the State and rights and responsibilities of the State of the Socialist Republic of Vietnam toward Vietnamese citizens.